Analysis of Rclone Implementation for File Sharing Security on OneDrive Cloud Storage - Widyawati, Lilik; Azwar, Muhammad; Alafi, Hairudin; Asif, Iqra (Jurnal Bumigora Information Technology (BITe), 2024)
Background: OneDrive provides a reliable infrastructure for storing and managing user data. However, along with the benefits, the security challenges associated with storing and sharing files in the cloud are also increasing. One of the main aspects of cloud storage security management is the file-sharing process. While OneDrive offers a few security features, such as access control and two-factor authentication, there remains a need to strengthen additional layers of security, especially when sharing files with external parties.Objective: This research aims to analyze the effectiveness of Rclone in improving file-sharing security on OneDrive, especially File Backup and File Encryption.Methods: This research uses the Network Development Life Cycle (NDLC) method, which includes six stages. This research focuses on three stages: analysis, design, and simulation prototyping.Result: The application of Rclone for file sharing security on OneDrive can increase data security in cloud storage, as evidenced by three backup attempts on .doc files with an average time of 2.033 seconds and successful encryption of 4 files with an average time of 37 seconds.Conclusion: Using Rclone as a tool to manage data security on OneDrive improves data protection and provides flexibility and efficiency in file management, making it an effective solution for file sharing security needs in cloud storage